Niger River Water Conflicts: Explanations and Forecasts (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
The Niger River basin home to more than 100 million people invites rigorous techniques to evaluate water conflicts among riparian areas. Conflict categories of trigger, casualty, and weapon in the interval of 2000-2022 are associated with riparian areas, revealing alternative results. The correspondence analysis reveals a relationship between riparian areas and conflicts depending on whether Benin and Niger are involved in no conflicts in the basin. The inclusion of some riparian areas in the same category implies that riparian areas with different domestic traits, such as population size, political regime, political stability, the number and length of shared borders, and the intensity of scarcity of water are similar in terms of conflicts. Future extensions of the analysis will include alternative factors, such as the destruction of nature, water pollution, and population growth, to assess water conflicts in the Niger River basin. Adding dimensions would help assess the future risks of water conflicts.